Qatar residents' satisfaction for using the Doha Metro Rail System: An analysis for sustainable transportation - Larry C. Flores; Ardvin Kester S. Ong; Maela Madel L. Cahigas; Ma. Janice J. Gumasing; Crisha Mae M. Cedron (Acta Psychologica)
Doha's public transportation system was entirely dependent on publicly run ground transportation services, including buses, taxis, and limousines before the Doha Metro Rail System – a sustainable transportation system, was implemented. This study integrated the Social Exchange Theory (SET) with the SERVQUAL 5 dimensions as a higher-ordered construct to assess how satisfied Qatar residents were with the Doha Metro Rail System after three years of service. To encourage commuters to use sustainable public transportation, it is imperative to design methods to assess public travel satisfaction concerning public transportation use as Qatar moves toward a sustainable public transportation system. An online adapted survey of 63 questions was completed by 319 residents of Qatar. The causal relationship between SERVQUAL dimensions, SET, and satisfaction was determined holistically by the application of structural equation modeling (SEM). The study's SEM output revealed that nine variables had significant effects on passengers' trust and satisfaction. These variables included accessibility, perceived economic benefit, crisis management, assurance, reliability, empathy, tangibles, and responsiveness. In addition, five (5) hypotheses were found to be significant. Crisis management, accessibility, and perceived economic benefits all had a considerable positive impact on passenger trust. Evidently, passenger trust has a favorable impact on customer satisfaction. Additionally, service quality and its domains have a substantial impact on passenger satisfaction. These findings provide a comprehensive picture of the elements that influence Qatar residents' satisfaction with the Doha Metro Rail System. Doha Metro service providers and authorities can use these findings to develop and improve public transportation for the benefit of passengers, service providers, and authorities, resulting in more sustainable public transportation.